Minimum Wage Determinations in The Regional Economic Development Structure: Central Java’s Longitudinal Analysis in 2020-2024 - Herlambang Bima Setya; Putri Patria Kusuma (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the factors influencing the MW and assess its role in regional economic development. Research Method: This study uses a quantitative approach with panel data regression. The estimation models used are the Fixed Effects Model (FEM) and the Random Effects Model (REM), with the independent variables being Regional Gross Domestic Product (GDRP), Labor Force Participation Rate (LFPR), Average Years of Education, Open Unemployment Rate (OUR), and Dependency Ratio. Results and Discussion: The results show that GDRP, LFPR, and the dependency ratio have a significant positive effect on the MW, while the LFPR has a significant negative effect. Average years of education has a positive but insignificant effect. Simultaneously, all variables have a significant effect on the Minimum Wage MW. Implications: These findings emphasize that determining the MW requires considering economic, employment, and demographic conditions in proportion. Originality: This study integrates regional economic, employment, and demographic factors to analyze minimum wage determination across 35 regencies/cities in Central Java Province, using panel data for the 2020–2024 period.